IMMEDIATE EFFECTS OF MANIPULATION OF TALUS ON BALANCE IN YOUNG ADULTS WITH ASYMPTOMATIC ANTERIOR TALUS (Fiep Bulletin - online, 2013)
Introduction: The ankle joint has an important role in the adjustment of postural balance in bipedal support because of its sensorimotor functions. It is believed that modifications of the talus bone biomechanics may lead to amendments in postural balance. Full range motion of dorsiflexion is essential to perform functional activities. Objective: To evaluate the immediate effects of the manipulation by mobilization and relocation of the talus on balance determined by analysis of postural center of pressure in young asymptomatic adults who have anterior talus. Methods: Male and female volunteers (n = 18) with biomechanical dysfunction in the talus were divided into three groups, intervention 1, intervention 2 and placebo. The diagnosis of dysfunction of the talus was performed by active dorsiflexion. A force plate was used to evaluate stabilometry and center of pressure data were analyzed. Impaction of the talus was the maneuver done in intervention 1, while anterior talus thrust was the maneuver done in intervention 2. The technique of impaction of the talus was only simulated in the placebo group. Both groups were evaluated by stabilometry before and after intervention. The tests were conducted under conditions of open and closed eyes. Results: The stabilometry rates showed no statistical differences between assessments. Conclusion: The manipulation through mobilization of the ankle (impaction of the talus) and relocation of the talus (anterior talus thrust) did not affect postural balance in young asymptomatic patients who have anterior talus.
Keywords: balance; ankle; osteopathic manipulation